Preparation and optimisation of palm kernel shell activated carbon for methane adsorption / Mohd Saufi Md Zaini - Md Zaini, Mohd Saufi (2016)
The storage of natural gas by adsorption has high potential to replace the compressed natural gas storage in mobile application. The adsorbed natural gas storage technology (ANG), the gas is stored through adsorption in porous material (e.g. activated carbon) at low pressure. However, its capacity and performance depend on the type of porous material, the method used for the preparation of adsorbent and the preparation conditions. This study focuses on the development of activated carbon from palm kernel shell activated carbon for methane storage. The preparation of activated carbon was divided into two phases according to its objectives. The first phase of preparation of activated carbon was conducted to study the effects of activation agents by CO2, steam and their sequential combinations on the pore development of activated carbon. The results show that the combination of CO2 and steam, regardless of their sequences, results in a higher carbon burn-off than the single activating agent. The combination of activation in the sequence of C02-steam, however, gives the highest value of carbon burn-off and produces activated carbon with the highest total pore volume and BET surface area. Steam activation favours the creation of new microporous structures, while CO2 activation tends to widen the existing pores leading to the formation of mesoporous structures. The second phase of the study employs the Taguchi orthogonal array to optimise the preparation of activated carbon for methane storage. The statistical results show that the optimised conditions are the impregnation ratio of 0.55, activation temperature of 900 °C and activation time of 150 min. The impregnation ratio has the most influenced effect on methane adsorption based on the highest difference in delta of the S/N ratio analysis. The result of experiment using optimum conditions falls within the predicted value of the developed model and therefore justifying the significance of the model. Higher storage capacity is obtained for activated carbon prepared at optimum conditions which has higher BET surface area and total pore volume. The highest methane uptake in this study was 145.89 V/V at 10 bars which is very close to the desired storage capacity for application of ANG. The equilibrium data of the adsorption characteristic in this study fitted favourably to the Freundlich isotherm.